Investigation of work–life integration on burnout symptoms in women physician runners: a cross-sectional survey study. Issue 1 (19th February 2021) - Uhlig-Reche, Hannah; Larson, Allison R; Silver, Julie K; Tenforde, Adam; McQueen, Alisa; Verduzco-Gutierrez, Monica
Abstract : Objective: To investigate which factors, from demographics to work–life integration, are associated with burnout symptoms among self-declared active women physicians practising in the USA. Methods: Cross-sectional study of those actively engaged in a social media group for women physician runners. Electronically surveyed using 60 questions covering demographics, compensation, debt and domestic responsibilities with burnout assessed by the Mini-Z Burnout Survey. Results: Of the 369 women meeting inclusion criteria as attending physicians practising in the USA, the majority reported being White (74.5%) and at least 6 years out from training (85.9%). There was a significant association of increased burnout level with working more hours per week and being responsible for a greater percentage of domestic duties (p<0.0001 and p=0.003, respectively). Both factors remained significant in a multivariable model (p<0.0001). Conclusion: By exploring burnout in the physically active, we are better able to investigate contributors to burnout despite healthy exercise habits. Increased burnout was significantly associated with greater domestic responsibility and hours working. These findings in women physician runners suggest that exercise alone may not control burnout. Poor work–life integration deserves attention as a burnout contributor in women physicians, potentially serving as a target for burnout prevention strategies.